Wenshen Xiaozheng Tang induces apoptosis and inhibits migration of ectopic endometriotic stromal cells. (24th December 2016) - Zhang, Zhenzhen; Cheng, Xiaolan; Gui, Tao; Tao, Jia; Huang, Meihua; Zhu, Li; Luo, Mei; Cao, Peng; Wan, Guiping
Abstract: Ethnopharmacological relevance: Wenshen Xiaozheng Tang (WXT), a traditional Chinese medicine prescription, exerted a good therapeutic effect on endometriosis. However, the underlying mechanism is unclear. In the present study, we sought to evaluate the effect of WXT on the proliferation and migration of ectopic endometriotic stromal cells and explore the potential molecular mechanism. Materials and methods: Primary stromal cells derived from ectopic endometriotic lesions of patients with endometriosis were isolated and cultured. The inhibition effect of WXT on cell proliferation was determined by MTT. Apoptosis of ectopic endometriotic cells treated with WXT was analyzed with Annexin V-FITC/7-AAD staining. The activation of caspases was detected by western blot analysis. The influence of WXT on migration of ectopic endometriotic cells was measured by scratch wound healing assay and Transwell assay. The DNA binding activity of NF-κB and the expression of nuclear p65 protein were determined by electrophoretic mobility shift assay and western blot analysis, respectively. The impact of WXT on the expression of NF-κB regulated gene products involved in apoptosis and migration was determined by western blot analysis. Results: WXT inhibited the proliferation of ectopic endometriotic cells in a time- and dose-dependent manner. In addition, WXT treatment resulted in significant induction of apoptosis through the activation of caspases and inhibition of migration in ectopic endometriotic cells. WXT notably suppressed constitutive NF-κB-DNA-binding activity as well as TNF-α induced nuclear translocation of NF-κB p65 subunit in ectopic endometriotic cells. Moreover, WXT diminished the expression of NF-κB regulated gene products involved in apoptosis and migration, including c-IAP1, c-IAP2, XIAP, survivin, Mcl-1, COX-2 and MMP-9. Conclusions: Our results indicate that WXT induces apoptosis and inhibits migration of ectopic endometriotic stromal cells. Graphical abstract: